History made conscious : politics of knowledge, politics of the past - Eley, Geoff (2023)
During the last fifty years, the writing of history underwent two massive transformations. First, powered by Marxism and other materialist sociologies, the great social history wave instated the value of social explanation. Then, responding to new theoretical debates, the cultural turn upset many of those freshly earned certainties. Each challenge was profoundly informed by politics - from issues of class, gender, and race to those of identity, empire, and the postcolonial. The resulting controversies brought historians radically changed possibilities - expanding subject matters, unfamiliar approaches, greater openness to theory and other disciplines, a new place in the public culture. History Made Conscious offers snapshots of a discipline continuously rethinking its charge. How might we understand "the social" and "the cultural" together? How do we collaborate most fruitfully across disciplines? If we take theory seriously, how does that change what historians do? How should we think differently about politics?